2016
DOI: 10.1155/2016/4140239
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Clavicula Pro Humero Reconstruction for Elderly Patients: Report of Two Cases

Abstract: Clavicula pro humero (CPH) reconstruction is a method that is used after proximal humeral excision. During CPH reconstruction, the ipsilateral clavicle is rotated downward and connected to the preserved distal humerus by using plates and screws. This method is frequently used for reconstruction surgeries involving young patients and has positive outcomes. In this study, we describe two cases of CPH reconstruction that were performed on elderly individuals after wide resection of the proximal humerus; postopera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…These published cases have revealed that CPH can maintain shoulder stability with comparable mobility (average 75° on flexion) and superior Musculoskeletal Tumor Society (MSTS) functionality scores (83%) [ 10 , 11 ]. However, the published complication rates for this procedure are high, with a substantial number of documented postoperative complications requiring surgical revision (Supplemental Table 1 ) [ 8 , 12 20 ]. The largest pediatric case series assessing postoperative outcomes following CPH for proximal humerus reconstruction revealed proximal nonunion requiring revision surgery occurred in five of seven patients (71%) [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…These published cases have revealed that CPH can maintain shoulder stability with comparable mobility (average 75° on flexion) and superior Musculoskeletal Tumor Society (MSTS) functionality scores (83%) [ 10 , 11 ]. However, the published complication rates for this procedure are high, with a substantial number of documented postoperative complications requiring surgical revision (Supplemental Table 1 ) [ 8 , 12 20 ]. The largest pediatric case series assessing postoperative outcomes following CPH for proximal humerus reconstruction revealed proximal nonunion requiring revision surgery occurred in five of seven patients (71%) [ 19 ].…”
Section: Introductionmentioning
confidence: 99%